Correction: Recommended reporting items for epidemic forecasting and prediction research: The EPIFORGE 2020 guidelines. - Simon Pollett; Michael A Johansson; Nicholas G Reich; David Brett-Major; Sara Y Del Valle; Srinivasan Venkatramanan; Rachel Lowe; Travis Porco; Irina Maljkovic Berry; Alina Deshpande; Moritz U G Kraemer; David L Blazes; et al. (PLoS Medicine, 2023)
[This corrects the article DOI: 10.1371/journal.pmed.1003793.].